Morbidity profile, hepatitis B vaccination and personal protective equipment usage among sweepers of a medical institute in central India: A cross-sectional study - Pradeep Kaswan; Prakash Bhatkule; Tuhina Shree; Shruti Agrawal; Souvik Manna (Clinical Epidemiology and Global Health, 2024)
Introduction: Health care workers are exposed to a variety of occupational risks making them susceptible to infections, besides being at risk of non-communicable diseases. The objectives of this study were to assess the morbidity pattern and associated factors among sweepers working at a tertiary care centre in Central India. Methods: A hospital-based cross-sectional study was conducted from September 2016 to September 2018 among 253 sweepers, who were administered a self-reported questionnaire. Information was collected related to demographic profile, use of personal protective equipment (PPE), vaccination status; and screening for co-morbidities was done using clinical examination and blood tests. Results: Mean duration of employment was 11.9 (±13.0) years. A total of 117 (46.2%) of the 253 sweepers reported one or more chronic conditions and 197 (77.9%) reported one or more systemic problems, most commonly musculoskeletal (113, 44.7%), cardio-vascular (68, 26.9%), ocular (44, 17.4%), dental (36, 14.2%), respiratory (28, 11.1%) and gastrointestinal disorders (16, 6.3%). Total 5s8 (22.9%) participants reported single and 80 (31.6%) reported multiple needlestick injuries, while only 77 (30.4%) had completed hepatitis-B vaccination schedule. Multivariable adjusted analysis revealed that age (Odds Ratio OR: 1.03, 95% CI: 1.00–1.06), male gender (OR: 3.11, 95% CI: 1.65–5.88) and waist hip ratio (OR: 433.19, 95% CI: 5.12–36622.87) were significant predictors of chronic conditions, while female gender, shorter length of service and knowledge about PPE were significant predictors of PPE usage. Conclusions: Most of the sweepers had at least one morbidity, highlighting the importance of periodic health check-ups, training, and awareness programmes. Provision of appropriate PPE and immunization with HBV is also recommended.